Comparison of bioavailability between β-cryptoxanthin and β-carotene and tissue distribution in its intact form in rats. Issue 2 (1st February 2014) - Sugiura, Minoru; Ogawa, Kazunori; Yano, Masamichi
Abstract: The bioavailability of two intact carotenoids in several tissues of β-cryptoxanthin- and β-carotene-fed rats (20 mg/kg of diet) was investigated. Although metabolites of provitamin A are not included in our study, β-cryptoxanthin was found at higher concentrations in majority of the tissues. The results show that the bioavailability of intact β-cryptoxanthin seemed to be higher than that of β-carotene.